Optimal. Leaf size=24 \[ \frac {1}{4} e^{-2-2 e^x} x \left (2-2 e^x x^2\right ) \]
________________________________________________________________________________________
Rubi [F] time = 0.53, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {1}{2} e^{-2-2 e^x} \left (1+2 e^{2 x} x^3+e^x \left (-2 x-3 x^2-x^3\right )\right ) \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {1}{2} \int e^{-2-2 e^x} \left (1+2 e^{2 x} x^3+e^x \left (-2 x-3 x^2-x^3\right )\right ) \, dx\\ &=\frac {1}{2} \int e^{-2 \left (1+e^x\right )} \left (1+2 e^{2 x} x^3+e^x \left (-2 x-3 x^2-x^3\right )\right ) \, dx\\ &=\frac {1}{2} \int \left (e^{-2 \left (1+e^x\right )}+2 e^{-2 \left (1+e^x\right )+2 x} x^3-e^{-2 \left (1+e^x\right )+x} x \left (2+3 x+x^2\right )\right ) \, dx\\ &=\frac {1}{2} \int e^{-2 \left (1+e^x\right )} \, dx-\frac {1}{2} \int e^{-2 \left (1+e^x\right )+x} x \left (2+3 x+x^2\right ) \, dx+\int e^{-2 \left (1+e^x\right )+2 x} x^3 \, dx\\ &=-\left (\frac {1}{2} \int \left (2 e^{-2 \left (1+e^x\right )+x} x+3 e^{-2 \left (1+e^x\right )+x} x^2+e^{-2 \left (1+e^x\right )+x} x^3\right ) \, dx\right )+\frac {1}{2} \operatorname {Subst}\left (\int \frac {e^{-2-2 x}}{x} \, dx,x,e^x\right )+\int e^{-2 \left (1+e^x-x\right )} x^3 \, dx\\ &=\frac {\text {Ei}\left (-2 e^x\right )}{2 e^2}-\frac {1}{2} \int e^{-2 \left (1+e^x\right )+x} x^3 \, dx-\frac {3}{2} \int e^{-2 \left (1+e^x\right )+x} x^2 \, dx-\int e^{-2 \left (1+e^x\right )+x} x \, dx+\int e^{-2 \left (1+e^x-x\right )} x^3 \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.18, size = 23, normalized size = 0.96 \begin {gather*} \frac {1}{2} e^{-2 \left (1+e^x\right )} \left (x-e^x x^3\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.55, size = 19, normalized size = 0.79 \begin {gather*} -\frac {1}{2} \, {\left (x^{3} e^{x} - x\right )} e^{\left (-2 \, e^{x} - 2\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.15, size = 32, normalized size = 1.33 \begin {gather*} -\frac {1}{2} \, {\left (x^{3} e^{\left (2 \, x - 2 \, e^{x}\right )} - x e^{\left (x - 2 \, e^{x}\right )}\right )} e^{\left (-x - 2\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.05, size = 19, normalized size = 0.79
method | result | size |
risch | \(\frac {\left (-{\mathrm e}^{x} x^{3}+x \right ) {\mathrm e}^{-2 \,{\mathrm e}^{x}-2}}{2}\) | \(19\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \frac {1}{2} \, {\rm Ei}\left (-2 \, e^{x}\right ) e^{\left (-2\right )} - \frac {1}{2} \, {\left (x^{3} e^{x} - x\right )} e^{\left (-2 \, e^{x} - 2\right )} - \frac {1}{2} \, \int e^{\left (-2 \, e^{x} - 2\right )}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 2.16, size = 18, normalized size = 0.75 \begin {gather*} -\frac {x\,{\mathrm {e}}^{-2\,{\mathrm {e}}^x-2}\,\left (x^2\,{\mathrm {e}}^x-1\right )}{2} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.20, size = 19, normalized size = 0.79 \begin {gather*} \frac {\left (- x^{3} e^{x} + x\right ) e^{- 2 e^{x} - 2}}{2} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________